A New Approach to Expanding Interior Green Areas in Urban Buildings - Chyi-Gang Kuo; Chien-Wei Chiu; Pei-Shan Chung (Buildings)
Countries worldwide have implemented regulations on the green coverage ratio of new buildings to address the urban heat island effect. For example, Taipei City mandates that the green coverage rate of new buildings must be between 40% and 70%, while Singapore requires a green coverage rate of 100% or higher. Consequently, building greening is now a regulatory requirement rather than a preference. This study focuses on developing an indoor light-emitting-diode (LED) hydroponic inverted planting system to utilize ceiling space for expanding green areas in buildings. The light source of this system is suitable for both plant growth and daily lighting, thereby reducing electricity costs. The watertight planting unit does not require replenishment of the nutrient solution during a planting cycle for small plants, which can reduce water consumption and prevent indoor humidity. The modular structure allows various combinations, enabling interior designers to create interior ceiling scapes. Additionally, it is possible to grow aromatic plants and edible vegetables, facilitating the creation of indoor farms. Consequently, this system is suitable for high-rise residential buildings, office buildings, underground shopping malls, and indoor areas with limited or no natural light. It is also applicable to hospitals, clinics, wards, and care centers, where indoor plants alleviate psychological stress and enhance mental and physical health.